High Energy Physics Essentials A Guide to HEP Research - Aubin, Christopher (Wiley, 2026)
Bridge coursework to research with foundational lattice QCD knowledge Advanced undergraduate physics students transitioning to research projects often lack the specialized knowledge needed for theoretical particle physics work. High Energy Physics Essentials: A Guide to HEP Research addresses this gap directly. Written by an award-winning physics educator and research mentor, this book provides the foundational concepts students need to engage in supervised lattice QCD research early in their academic careers. The book reviews special relativity, electrodynamics, and quantum electrodynamics before introducing fundamental quantum chromodynamics concepts. Students learn the theory underpinning the standard model of elementary particle physics, including quarks as building blocks of protons, neutrons, and pions. Each chapter includes ten to twenty problems that reinforce material and provide practical experience solving theoretical physics problems. Readers will also find: Comprehensive coverage spanning special and general relativity, quantum mechanics, electrodynamics, quantum field theory, and essential group theory foundations Independent study structure allowing students to prepare for research projects without requiring additional coursework or direct supervision Practical problem sets in each chapter providing hands-on experience with the mathematical challenges inherent in theoretical particle physics Clear pathways from standard coursework to active participation in supervised lattice quantum chromodynamics research projects Guidance for supervisors seeking to close knowledge gaps when students transition from classroom learning to research environments Designed for advanced undergraduate physics students or even early graduate students preparing for research projects, this book also serves physicists and lecturers supervising student researchers. By equipping students with skills and confidence for theoretical particle physics research, it streamlines the transition from coursework to productive research participation.